HUMAN RESOURCE MANAGEMENT TRAINING IN THE DIGITAL ERA FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) SUPPORTED BY THE COOPERATIVES AND SMALL BUSINESS OFFICE: AN APPROACH TOWARDS ORGANIZATIONAL EFFECTIVENESS AND ADAPTATION TO TECHNOLOGICAL CHANGES - Fitri Melawati (Adisam Publisher, 2025)
The digital era presents unprecedented challenges and opportunities for Micro, Small, and Medium Enterprises (MSMEs) in adapting to rapid technological transformations. This qualitative library research examines the critical role of human resource management (HRM) training in enhancing organizational effectiveness and technological adaptation. By systematically analyzing existing literature, policy documents, and scholarly research, the study explores strategic approaches to developing workforce capabilities in the digital landscape. The research synthesizes contemporary theoretical frameworks and empirical insights to understand the impact of targeted HRM training programs on organizational resilience and technological integration.